Genetic variants in CCL5 and CCR5 genes and serum VEGF-A levels predict efficacy of bevacizumab in metastatic colorectal cancer patients - Suenaga, Mitsukuni (Int J Cancer, 2018)
Early VEGF-A reduction (EVR) by targeting abundant VEGF-A is a potential predictive marker of bevacizumab (BEV). The CCL5/ CCR5 axis modulates VEGF-A production via endothelial progenitor cells migration. We tested whether genetic polymorphisms in the CCL5/CCR5 pathway could predict efficacy of BEV in patients with metastatic colorectal cancer (mCRC) in a first-line setting. Genomic DNA was extracted from 215 samples from three independent cohorts: 61 patients receiving FOLFOX+BEV (evaluation cohort); 83 patients receiving FOLFOX (control cohort); 71 patients receiving FOLFOX/XELOX+BEV (exploratory cohort) for validation and serum biochemistry assay (n = 48). Single nucleotide polymorphisms of genes in the CCL5/CCR5 pathway were analyzed by PCR-based direct sequencing. Considering the unbalanced distribution of patient baseline characteristics between the evaluation and control cohorts, propensity score matching analysis was performed. Serum VEGF-A levels during treatment were measured using ELISA. Among the evaluation and control cohorts, patients with any CCL5 rs2280789 G allele had longer progression-free survival (PFS) and overall survival (OS) when receiving FOLFOX+BEV than FOLFOX (PFS: 19.8 vs. 11.0 months, HR 0.44, 95%CI: 0.24–0.83, p = 0.004; OS: 41.8 vs. 24.5 months, HR: 0.50, 95%CI: 0.26–0.95, p = 0.024). No significant difference was shown in patients with the A/A variant. In the exploratory cohort, CCL5 rs2280789 G alleles were associated with higher VEGF-A levels at baseline and a greater decrease in VEGF-A levels at day 14 compared to the A/A variant. CCL5 and CCR5 impact the angiogenic environment, and the genotypes in CCL5/CCR5 genes may identify specific populations who will benefit from BEV in first-line treatment for mCRC.